Developing entrepreneurial ecosystems in academia - Tunio, Muhammad Nawaz; Shaikh, Erum; Chaudhary, Kiran; Tiep, Le Thanh (IGI Global, 2022)
"This book discusses academic entrepreneurship that focuses on the educated population who are learning and working in the universities and how they can create an entrepreneurial ecosystem so that academics can establish the role of entrepreneurship after teaching and research